Identification As a Model for Traditional Art Studies - Sugito, Bambang; Sasanadjati, Jajuk; Hidajad, Arif; Putra, Budi (Proceeding Series of International Conference on Arts and Humanities, 2021)
Traditional arts in various regions are rarely recognized as a whole as a source of knowledge. There are many traditional arts that have not been written as literacy in traditional society. So that the generation does not understand the traditional arts in their environment. Identification is a model that is used to sort from various aspects. So that it can sort from the aspect of the region, type, form and motion used in traditional arts. Identification is the sorting of an object that requires analysis related to research needs. The results of the identification can be used as a basis for research. The identification results can be used as an introduction to students, the community and generations of society to explore traditional arts.